Enterprise Surveys : Azerbaijan Country Profile 2013 - World Bank; International Finance Corporation (Washington, DC, 2014)
The country profile for Azerbaijan is based on data from the enterprise surveys conducted by the World Bank in 2013. The enterprise surveys focus on the many factors that shape the decisions of firms to invest. These factors can be accommodating or constraining and play an important role in whether a country will prosper or not. An accommodating business environment is one that encourages firms to operate efficiently. Such conditions strengthen incentives for firms to innovate and to increase productivity, key factors for sustainable development. A more productive private sector, in turn, expands employment and contributes taxes necessary for public investment in health, education, and other services. In contrast, a poor business environment increases the obstacles to conducting business activities and decreases a country's prospects for reaching its potential in terms of employment, production, and welfare. Enterprise surveys are conducted by the World Bank and its partners across all geographic regions and cover small, medium, and large companies. The surveys are applied to a representative sample of firms in the non-agricultural economy. The sample is consistently defined in all countries and includes the entire manufacturing sector, the services sector, and the transportation and construction sectors. Public utilities, government services, health care, and financial services sectors are not included in the sample. Enterprise surveys collect a wide array of qualitative and quantitative information through face-to-face interviews with firm managers and owners regarding the business environment in their countries and the productivity of their firms. The topics covered in enterprise surveys include the obstacles to doing business, infrastructure, finance, labor, corruption and regulation, law and order, innovation and technology, trade, and firm productivity.